Effect of different nanostructured SiC on thermal, ablation and char layer mechanical properties of ethylene propylene diene monomer composites. Issue 6 (28th April 2022) - Kun, Hui; Li, Jiang; Yan, Ning; Bian, Cheng; Guan, Yiwen; Yang, Yanjing; Li, Hongyan
Abstract: SiC nanowire (SiC‐NW) and SiC nanopowder (SiC‐NP) were used to reinforce ethylene propylene diene monomer (EPDM) composites to improve their ablation and erosion resistance. The mechanical and thermal properties of the composites were investigated. The ablation resistance and thermal insulation performance of the composites were evaluated based on the oxyacetylene ablation and ablation motor experiments. In addition, the particle erosion resistance of the char layer was characterized. The test and experimental results show that, compared with the basic formulation, the ablation resistance of the formulations containing SiC‐NW and SiC‐NP increased by 85.54% and 71.08%, respectively. The particle erosion resistance of the char layer increased by 80.61% and 63.39%, respectively. Meanwhile, the SiC nanofiller reduced the thermal insulation performance of the EPDM composites. Compared with the basic formulation, the maximum back temperature of the SiC‐NW and SiC‐NP formulations increased by 39.23% and 13.08%, respectively. It inferred that during the ablation process, the SiC nanofiller can not only promote the deposition reaction of pyrolysis gas, but also react with oxidizing components and the char layer at different temperatures, thus improving the ablation resistance of the EPDM composites and the strength of the char layer. However, the high thermal conductivity of SiC nanofiller reduces the thermal insulation performance of the composites. Abstract : 1. SiC nanowire and SiC nanopowder are used to reinforce ethylene propylene diene monomer composites to improve their ablation and erosion resistance. 2. SiC nanowire reduces the thermal insulation performance of the composite materials. 3. SiC nanowire reinforce the mechanical of char layer of the composite materials.